2017
DOI: 10.3847/2041-8213/aa62fb
|View full text |Cite
|
Sign up to set email alerts
|

Radio-interferometric Monitoring of FRB 131104: A Coincident AGN Flare, but No Evidence for a Cosmic Fireball

Abstract: The localization of fast radio bursts (FRBs) has been hindered by the poor angular resolution of the detection observations and inconclusive identification of transient or variable counterparts. Recently a γ-ray pulse of 380 s duration has been associated with FRB 131104. We report on radio-continuum imaging observations of the original localization region of the FRB, beginning three days after the event and comprising 25 epochs over 2.5 years. We argue that the probability of an association between the FRB an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 53 publications
(85 reference statements)
0
26
0
Order By: Relevance
“…The emission is consistent with a gamma ray burst (GRB). The presence an expected multi-wavelength afterglow was not observed (Shannon and Ravi, 2017), but arguably may not be observable (Gao and Zhang, 2017). A high-energy (GeV) γ-ray afterglow is not affected by environment density, but searches for such signals have yielded null results (Xi et al, 2017).…”
Section: Frb 131104mentioning
confidence: 96%
“…The emission is consistent with a gamma ray burst (GRB). The presence an expected multi-wavelength afterglow was not observed (Shannon and Ravi, 2017), but arguably may not be observable (Gao and Zhang, 2017). A high-energy (GeV) γ-ray afterglow is not affected by environment density, but searches for such signals have yielded null results (Xi et al, 2017).…”
Section: Frb 131104mentioning
confidence: 96%
“…The association claim was however refuted [32] based on the non-detection of a radio afterglow at the location of the gamma-ray transient and the discovery of an AGN both temporally and spatially coincident with the FRB. Data taken with the Fermi gamma-ray burst monitor was searched for gamma-ray bursts associated with the repeating FRB 121102 during the time it was visible to the Fermi sky [22].…”
Section: Emission In Other Wavebands? What Are the Prospects For Fermi?mentioning
confidence: 99%
“…The follow-up observations performed by the XRT and the UVOT on board Swift two days after Swift was triggered by Swift J0644.5-5111 didn't detect X-ray and optical counterparts (DeLaunay et al 2016). Shannon & Ravi (2017) observed the 5.5 GHz and 7.5 GHz counterparts of FRB 131104 three days to 2.5 years after the FRB trigger and found that the upper limits of the 5.5 GHz and 7.5 GHz are 70 µJy and 100 µJy, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…A powerful tool to determine the progenitor system of Swift J0644.5-5111 is to research the properties of its environment, e.g., the number density (n) of the interstellar medium (ISM) surrounding the progenitor. Assuming that Swift J0644.5-5111 was associated with FRB 131104 and using the upper limit of 5.5 GHz counterpart of FRB 131104 reported by Shannon & Ravi (2017), Murase et al (2017) constrained the density of the ISM of FRB 131104 with the external shock model of afterglows and concluded that n 2 × 10 −3 cm −3 . By using the same model and the upper limits of radio counterparts and adopting different values of redshift, the fraction of energy in magnetic field (ε B ), and the fraction of energy in electrons (ε e ), Gao & Zhang (2017) constrained the parameter space of the ISM density.…”
Section: Introductionmentioning
confidence: 99%